2018
DOI: 10.3892/ijmm.2018.3411
|View full text |Cite
|
Sign up to set email alerts
|

β-glucans and cholesterol (Review)

Abstract: Hypercholesterolemia is one of primary risk factors of cardiovascular disease, together with metabolic syndrome, hypertension and diabetes. Although progress has been made, the search for novel methods of preventing and treating dyslipidemia is ongoing and current therapies for cardiovascular disease induce various side effects. β-glucans are linear unbranched polysaccharides found in various natural sources, such as mushrooms. Due to their structure they are able to interact with innate immunity receptors, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 149 publications
0
78
0
9
Order By: Relevance
“…In fact, the SC used in this study contained 23.2 g b-glucan per 100 g dry powder. Sima et al reviewed the effects of b-glucans on cholesterol balance in the body 36 and found b-glucans bind to bile acids, thereby promoting lipid excretion into feces, and induce cholesterol biosynthesis. Given that bile acids have an important role in cholesterol metabolism, further studies are needed to investigate how dietary SC affects lipid metabolism via bile acid metabolism, including synthesis and secretion into bile.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the SC used in this study contained 23.2 g b-glucan per 100 g dry powder. Sima et al reviewed the effects of b-glucans on cholesterol balance in the body 36 and found b-glucans bind to bile acids, thereby promoting lipid excretion into feces, and induce cholesterol biosynthesis. Given that bile acids have an important role in cholesterol metabolism, further studies are needed to investigate how dietary SC affects lipid metabolism via bile acid metabolism, including synthesis and secretion into bile.…”
Section: Discussionmentioning
confidence: 99%
“…β-Glucans have many bioactivities including antidiabetes; anticancer; antiobesity; anti-inflammation; immunomodulation; cardioprotection; lower cholesterol and lower blood pressure; improve bowel health, gastroprotection, and hepatoprotection; reduce chronic kidney disease and metabolic syndrome; prevent the risk of heart and cardiovascular diseases; and accelerate wound healing activities (Figure 1, Tables 2 and 3) [13,18,98,111,116,122,123,127,133,[143][144][145][146][147][148][149]. The major mechanisms of β-glucans of barley involve in the prevention of chronic diseases are as follows: β-glucans can interact with intestinal lipids and bile salt to reduce cholesterol levels and subsequently prevent diabetes, hypertension, cardiovascular disease, and metabolic syndrome [143]. Barley β-glucans not only control appetite and improve insulin sensitivity by gut hormone secretion via microbiota produced SCFA [144] due to its high molecular weight and high viscosity but also increase their antigen ability and enhances the proinflammatory cytokines, which can be degraded by macrophages and natural killer cells mediating its cellular cytotoxicity opsonized tumor cells [145].…”
Section: Major Mechanisms Of Functional Ingredients In Barleymentioning
confidence: 99%
“…No obstante, los demás grupos tratados con la polidextrosa (HC4%P y HC6%P) no tuvieron diferencia en relación al control, coincidiendo con el estudio de Pronczuk y Heys 18 . A pesar de conflictivo, se sabe que las fibras solubles tienen efectos en el control de los triglicéridos, además de la importante característica hipocolesterolémica, como la reducción del colesterol total y del LDL, y el aumento del HDL, siendo factores importantes en el control de las dislipidemias 25,26 . Hay muchas explicaciones a respecto del efecto hipocolesterolémico de las fibras.…”
Section: Parámetrosunclassified